2017
DOI: 10.1002/2017jb014047
|View full text |Cite
|
Sign up to set email alerts
|

A 15 year catalog of more than 1 million low‐frequency earthquakes: Tracking tremor and slip along the deep San Andreas Fault

Abstract: Low‐frequency earthquakes (LFEs) are small, rapidly recurring slip events that occur on the deep extensions of some major faults. Their collective activation is often observed as a semicontinuous signal known as tectonic (or nonvolcanic) tremor. This manuscript presents a catalog of more than 1 million LFEs detected along the central San Andreas Fault from 2001 to 2016. These events have been detected via a multichannel matched‐filter search, cross‐correlating waveform templates representing 88 different LFE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 71 publications
(165 citation statements)
references
References 67 publications
8
156
0
Order By: Relevance
“…The catalog includes over one million earthquakes recorded since 2001; however, we limit our analysis to between 2006 and May of 2016 to minimize the effect of afterslip from the 2004 M6 Parkfield earthquake. Additionally, estimated LFE source dimensions of hundreds of meters (e.g., Bostock et al, 2015;Thomas et al, 2016) are typically less than LFE location uncertainties of 1-2 km (Shelly, 2017). The time series of cross correlations for each template are then summed over each station and channel to create a network cross-correlation time series.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalog includes over one million earthquakes recorded since 2001; however, we limit our analysis to between 2006 and May of 2016 to minimize the effect of afterslip from the 2004 M6 Parkfield earthquake. Additionally, estimated LFE source dimensions of hundreds of meters (e.g., Bostock et al, 2015;Thomas et al, 2016) are typically less than LFE location uncertainties of 1-2 km (Shelly, 2017). The time series of cross correlations for each template are then summed over each station and channel to create a network cross-correlation time series.…”
Section: Methodsmentioning
confidence: 99%
“…The LFE catalog used in this study can be found in the supporting information of Shelly (2017). A. M. T. and Q.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The semidiurnal period is more than 2 orders of magnitude longer than the average episode duration of 302 s, meaning that to first order, all of the LFEs in each episode occur at the same time relative to the tidal period. To avoid possible influences of the 2004 Parkfield earthquake (e.g., Shelly, 2017) we undertake the analysis from 2005.5 (07/02/05) to the end of the catalog (1/4/2012). The average recurrence interval in this family is 3.4 days, intermediate between the semidiurnal and fortnightly tides.…”
Section: Catalog Processingmentioning
confidence: 99%
“…The central San Andreas LFE catalog (Shelly & Hardebeck, 2010;Shelly, 2017) was used in this paper. That data and the technical aspects of catalog generation are available in those publications and their supplements.…”
Section: Acknowledgmentsmentioning
confidence: 99%